Cooperative brand alliances: how to generate positive evaluations - Dickinson, Sonia; Heath, Tara (ANZMAC, 2008)
This paper examines consumer evaluations of cooperative branding alliances (co branding) in a consumer marketing context. These co branding alliances are described as the pairing of two or more brands to form a separate and unique product, with their success being reliant on producing positive consumer evaluations. Data was gathered from 194 respondents with qualitative and quantitative findings showing that in order to achieve positive consumer evaluations of co branded offerings, brand partners independently require positive parent brand attitudes as a precondition. Furthermore, high levels of perceived parent brand fit is also a requisite for creating favourable co brand evaluations, albeit the moderating influence of ‘parent brand fit’ on how consumers evaluate co brands received mixed results.